The Effect of Crawford Series Teaching (CST) on the Students’ Writing Achievement - Aswadi Jaya; Hermansyah Hermansyah; Asti Veto Mortini (Esteem Journal of English Education Study Programme, 2018)
Abstract: This experimental study aimed to investigate if there was any significant difference in writing ability between the students who were taught by Crawford series Teaching technique and those who were taught by using individual writing technique. Two classes of the first grade students of SMAN 5 Palembang were selected randomly as the sample of the study; experimental and control groups. Each group consisted of 28 students. The instrument used in this study was a set of pre and post-tests. This study used t-test to see the difference achievement between experimental and control groups in terms of writing descriptive paragraph. The result showed that the students in EG achieved better performance in writing descriptive paragraph. P-value got from T-test was 0.02; it was less than the level of significance (0.05). Furthermore, the mean score of the post-test of the EG increased 13.35 points compared to the pre-test, while there was a progress of 6.67 points in the CG. The result also showed a great improvement in the five aspects of writing (content and mechanical, organization, vocabulary, and grammar. In conclusion, students’ achievement in writing descriptive paragraph improved significantly through Crawford Series Teaching technique.